Implications of Covid-19 on Auditor’s Reporting - Mila Austria Reyes; Hajanirina Andrianantenaina; Gatot Imam Nugroho (JAAF (Journal of Applied Accounting and Finance), 2021)
AbstractTwenty years ago, nobody will ever think that the world will experience what we are experiencing right now.  The whole world had been put in uncertainty due to pandemic which started from the city of Wuhan, China. This pandemic called COVID-19 had affected everyone’s life including many companies in Indonesia.  It has impact on audit quality. Matters are analyzed through input/output based on Francis (2011) and Knechel (2010). This research adopts desk study method to investigate the impact of COVID-19 to audit quality.  It suggests the improvement of the regulations (time, and fee), the auditor’s matters (experience, routine, and client). Quality can be based not only by the auditing report as the product from the activity, but from the engagement from the output of this report for long term horizon.